Age Management in Danish Companies: What, How, and How Much? - Jensen, Per H.; Møberg, Rasmus Juul (Nordic Journal of Working Life Studies, 2012)
This article investigates Danish employers’ behavior in the area of active aging, which is made topical by demographic aging. It describes age management practices and explains why some companies are more prone to employ age management than others. The study is based on a survey conducted among a representative sample of Danish employers, and 609 interviews in total have been carried out. Data have been scrutinized using frequency analysis for descriptive purposes as well as binary logistic regression analysis for explanatory purposes. Findings indicate that structural, cognitive, and action-oriented variables have significance for whether companies develop and employ active age management policies.